Solid waste management at the RS Jogja and RS PKU Muhammadiyah in jogja - Muchsin Maulana; Hari Kusnanto; Agus Suwarni (Faculty of Medicine, Universitas Islam Indonesia, 2015)
Background: In daily activities, the hospital produces significant amount of waste which, if not properly discharged or burned, may cause adverse effect on workers as well as the surrounding area. So it is needed to explore the treatment process of waste at the RS PKU Muhammadiyah Jogja and RS Jogja.Objective: The aim of this study was to get a clear picture or description on waste management techniques at the RS PKU Muhammadiyah Jogja and RS Jogja. Methods: This study used a qualitative descriptive case study. Data were obtained through observation, document studies, in-depth interviews with the head of Environmental Health Installation and Waste Management Staffs, as well as data in the form photos and recordings. Result: Extermination of waste is executed by entering one by one parcel of medical solid waste into incinerator. The range of temperatures inside the incinerator is 600°C - 800°C. Combustion is performed approximately six hours. During the culling takes place, incinerator operators supervise the combustion process from a room that is close to the incinerator directly. Combustion process of infectious solid waste is carried out in RS PKU by PT Jasa medivest whereas hazardous and toxic waste by PT Arah. Conclusion: Each Hospital, RS PKU Muhammadiyah Jogja and RS Jogja already has a clear Standard Operating Procedure (SOP), but RS Jogja has better SOP and Implementation and Technical Guidelines in comparison with RS PKU Muhammadiyah Jogja.